2018
DOI: 10.1016/j.neuron.2018.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Vision and Locomotion Shape the Interactions between Neuron Types in Mouse Visual Cortex

Abstract: SummaryCortical computation arises from the interaction of multiple neuronal types, including pyramidal (Pyr) cells and interneurons expressing Sst, Vip, or Pvalb. To study the circuit underlying such interactions, we imaged these four types of cells in mouse primary visual cortex (V1). Our recordings in darkness were consistent with a “disinhibitory” model in which locomotion activates Vip cells, thus inhibiting Sst cells and disinhibiting Pyr cells. However, the disinhibitory model failed when visual stimuli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
303
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(354 citation statements)
references
References 60 publications
46
303
5
Order By: Relevance
“…Many of these studies used anesthetized preparations, making comparisons with our results difficult, but our data are consistent with previous reports of small differences in overall activity between natural vision and complete darkness in awake animals (8) and sparse modulation of spiking in response to natural scene viewing (12,(45)(46)(47). In general, our data support the view that mean firing rates in V1 can be stabilized over both long (13) and short timescales without interfering with visual coding, which may arise through very sparse modulation of spiking and/or higher-order population dynamics (46,48,49). Despite the lack of robust changes in firing rates across the population at D-L transitions, we did observe a small subset of neurons that transiently increased their firing specifically at the appearance of visual input (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Many of these studies used anesthetized preparations, making comparisons with our results difficult, but our data are consistent with previous reports of small differences in overall activity between natural vision and complete darkness in awake animals (8) and sparse modulation of spiking in response to natural scene viewing (12,(45)(46)(47). In general, our data support the view that mean firing rates in V1 can be stabilized over both long (13) and short timescales without interfering with visual coding, which may arise through very sparse modulation of spiking and/or higher-order population dynamics (46,48,49). Despite the lack of robust changes in firing rates across the population at D-L transitions, we did observe a small subset of neurons that transiently increased their firing specifically at the appearance of visual input (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Recent work has suggested a model where VIP-INs regulate cortical circuits predominantly by inhibiting other interneurons, including the dendrite-targeting SST-INs (Pfeffer et al, 2013), thereby disinhibiting pyramidal neurons (though see (Polack et al, 2013) and (Dipoppa, 2016) for a different conclusion). We found that VIP-INs in mutants received decreased glutamatergic, but not cholinergic, synaptic input and were not appropriately activated at locomotion onset, suggesting that their impact on the local neural circuit was diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in awake mice have revealed that locomotion [1][2][3] , shifts of arousal [4][5][6] , motor activity 7 , and behavioral tasks [8][9][10][11][12] modulate sensory responses. These and other studies in transgenic mice have further uncovered the role of cortical neuronal subtypes 13,14 during sensory response modulation. However, it remains unknown whether cortical circuits in mice selectively enhance sensory responses to stimuli in discrete regions of space, as classically observed in primates during selective attention tasks.…”
mentioning
confidence: 81%